Perpetuating Inequality: Junior Women Do Not See Queen Bee Behavior as Negative but Are Nonetheless Negatively Affected by It - Sterk, Naomi; Meeussen, Loes; Van Laar, Colette (Frontiers in Psychology, 2018)
Previous research has revealed that women may attempt to avoid negative gender stereotypes in organizations through self-group distancing, or “queen bee”, behaviors: emphasizing masculine qualities, distancing themselves from other women, and legitimizing organizational inequality. Factors that increase self-group distancing have been identified (e.g., existing discrimination and low group identification), but it is unknown how self-group distancing by an ingroup leader is perceived by and affects subordinates of the negatively stereotyped group. In the current study, female participants received ambiguous negative feedback from a male versus female leader displaying queen bee-type versus neutral behavior. As expected, a male leader displaying queen bee-type behavior was seen as having less positive intent than a male leader displaying neutral behavior, which in turn increased how sexist he was perceived to be. A female leader displaying queen bee (vs. neutral) behavior was not seen as having less positive intent, which thus did not indirectly influence perceived sexism. Behavior of both male and female leaders did affect junior women: Participants exposed to a leader displaying queen bee-type behavior reported more anger, sadness, and anxiety than participants exposed to a leader displaying neutral behavior. These data provide further evidence that simply adding more women or minorities in key senior positions is insufficient to change inequality if bias in the organization is not tackled. Specifically, exposure to gender inequality can steer female leaders to endorse–rather than change–stereotypes about women, and this behavior is particularly consequential because it a) might not be recognized as bias and b) exerts negative effects.